Innovation System Wind Energy Industry - Gnauck, Robert; Hnilica, Jiří, 1976-; Martina, Jakl; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The wind industry has arrived at a state of technological maturity and is occasionally already today cost-competitive to conventional sources of energy. This thesis investigates the process of innovation that took place within the industry. A theoretical background into economical theory of innovation together with a status quo assessment of today's wind industry serves as introduction to the topic. In the analytical part, inducement mechanisms and functions of technological development will be identified as crucial drivers for innovation within the sector. The key findings of this thesis lead to conclude that it is now the responsibility of the industry to becoming fully cost-competitive to conventional sources. The advancement of technological lifecycle will primarily depend on turbine manufacturers and their capability to drive innovation more independently from governments.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses